A Comparative Sociolinguistic Analysis of Indonesian and Local Language Use: Evidence from Public and Islamic Boarding Schools in Gunungputri - Aulia Valentina; Trya Minda Insari; Dhea Yuniar Yuninta (JPI: Jurnal Pustaka Indonesia, 2025)
This study investigates the dynamics of language use and attitudes toward bilingual practices in two contrasting institutional contexts in Indonesia: a public junior high school (SMPN 04 Gunungputri) and an Islamic boarding school (Pesantren Rumah Al-Qur’an Daarut Tarbiyah). Guided by sociolinguistic theories of language shift and maintenance, the research explores how national and local languages interact within educational and domestic domains. Employing a mixed-method design with survey questionnaires and descriptive statistical analysis, data were collected from students in both institutions to examine intergenerational transmission, language practices at school and home, and attitudes toward bilingualism. The results indicate that while Bahasa Indonesia overwhelmingly dominates in formal educational settings, local languages remain vital in home and community domains, with maternal figures playing a central role in intergenerational transmission. Students across both institutions expressed strongly positive attitudes toward bilingual practices, high confidence in using both languages, and firm resistance to eliminating local languages. Notably, pesantren students demonstrated stronger endorsement of the benefits of bilingualism compared to their counterparts in public schools, suggesting that religious schooling may reinforce rather than diminish multilingual repertoires. These findings highlight the complex interplay between institutional environments, national policies, and cultural identity in shaping linguistic behavior. The study implies that policies to sustain linguistic diversity should move beyond family and community spheres by incorporating local languages into school curricula and extracurricular activities, thereby strengthening both cultural heritage and national cohesion